RESERVOIR QUALITY OF R1 RESERVOIR IN X FIELD OF THE WEST BARAM DELTA - ABDUL RAHIM, NAJMUDDIN (2020)
The R1 reservoir is characterised as a clastic reservoir of prograding sequence stratigraphic depositional settings.